Peningkatan Mutu Barang secara Kualitatif sebagai Upaya Perlindungan Konsumen di Bidang Metrologi - Sasi Azhari Kirana Putri (Asosiasi Riset Ilmu Teknik Indonesia, 2026)
Consumer protection is a crucial aspect of trade and industrial activities to ensure consumers’ rights to quality, safety, and fairness in obtaining goods. In the field of metrology, qualitative improvement of product quality plays a strategic role as a preventive effort to minimize consumer losses caused by unfair or non-compliant trading practices. This is in line with Law Number 8 of 1999 on Consumer Protection, which emphasizes legal certainty, honesty, and the responsibility of business actors toward consumers. This study aims to examine qualitative product quality improvement as an effort to realize consumer protection in the field of metrology. The research employs a qualitative descriptive approach through literature review and analysis of regulations, policies, and the role of metrological institutions in supervising product quality. The discussion focuses on compliance with standards, supervisory mechanisms, and the responsibility of business actors as key elements of consumer protection. The findings indicate that qualitative improvement of product quality contributes to fair transactions, enhances consumer trust, and prevents practices that may harm consumers. This study is expected to serve as a reference for relevant institutions in strengthening the role of metrology as an integral part of the consumer protection system.